Urinary Vitamin-D Binding Protein as an Early Predictor of Diabetic Nephropathyin Type 1 and Type 2 Diabetes - Sheet Saleh, Madha Mohammed; AL-Karawi, Isam Noori Salman; Alkhafajy, Haael Subhi Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Diabetic nephropathy (DN) is the most common microvascular complication that may lead to chronic renal failure in diabetic patients. Till now microalbuminuria, with its restrictions, is the early marker of DN, appeared after the disease exacerbation. Thus, new biomarkers are required to predict the early onset of DN before the appearance of microalbuminuria. The aim of this study is to investigate the possible use of uVDBP in the early prediction of DN. Fifty diabetic patients with DN and 40 diabetic patients without DN for both types of diabetes were enrolled in this study. All patients were tested for uACR, uVDBP (measured by ELISA), and blood HbA1c. The results demonstrated a highly significant elevation of uACR, HbA1c and uVDBP in diabetic patients with DN compared to those without DN. uVDBP exhibited a strong positive correlation with HbA1c and uACR in DN patients. ROC curve analysis showed a greater AUC (0.93), and cutoff value was >152 ng/ml with 94% sensitivity and 82% specificity for early detection of DN. These findings suggesting the sensitive and potential role of uVDBP in the early prediction and diagnosis of DN in type 1 and type 2 diabetes.